A Tale of Two Bloggers: Free Speech and Privacy in the Blogosphere - Daniel J. Solove (Washington University Law Review, 2006)
It is true that existing law lacks nimble ways to resolve disputes about speech and privacy on the Internet. Lawsuits are costly to litigate, and being sued can saddle a blogger with massive expenses. Bloggers often don’t have deep pockets, and therefore it might be difficult for plaintiffs to find lawyers willing to take their cases. Lawsuits can take years to resolve. People seeking to protect their privacy must risk further publicity in bringing suit. These are certainly serious problems, but the solution shouldn’t be to insulate bloggers from the law. The solution is to create a system for ensuring that bloggers blog responsibly without the law’s cumbersome costs. Perhaps systems of alternative dispute resolution could be used.
Keywords: Internet & amp; privacy; Freedom of speech; Blogs; Right of privacy; United States Constitution; United States